2014
DOI: 10.1007/s11356-014-3378-6
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic and environmental assessment of sewage sludge wet oxidation

Abstract: Today, several technologies and management strategies are proposed and applied in wastewater treatment plants (WWTPs) to minimise sludge production and contamination. In order to avoid a shifting of burdens between different areas, their techno-economic and environmental performance has to be carefully evaluated. Wet oxidation (WO) is an alternative solution to incineration for recovering energy in sewage sludge while converting it to mostly inorganic residues. This paper deals with an experimentation carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The operation cost for P recovery process was assumed as 9.0 USD/1kg P recovered for Airprex, and 17.8 USD/1 kg P recovered for Gifhorn (Egle et al, 2016). Prices for chemicals were referred to the literature values by Lorenzo-Toja et al, 2016a;Awad et al, 2019;Bertanza et al, 2014. 1 kWh of electricity in Malaysia costs 0.15 USD (United States dollar).…”
Section: Economic Assessmentmentioning
confidence: 99%
“…The operation cost for P recovery process was assumed as 9.0 USD/1kg P recovered for Airprex, and 17.8 USD/1 kg P recovered for Gifhorn (Egle et al, 2016). Prices for chemicals were referred to the literature values by Lorenzo-Toja et al, 2016a;Awad et al, 2019;Bertanza et al, 2014. 1 kWh of electricity in Malaysia costs 0.15 USD (United States dollar).…”
Section: Economic Assessmentmentioning
confidence: 99%
“…Proper sludge management is a key factor in the design and operation of wastewater treatment plants (WWTPs). Being sludge management costs as high as 40–60% of the WWTP total operating costs and due to environmental restrictions, significant reduction of sludge production is seen as providing a consistent economic advantage (Bertanza et al , 2015; Wang et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the WO of activated sludge was investigated [8][9][10] . It has been reported that the high biodegradability of WO effluent is well known as a carbon source for the denitrification process for the wastewater treatment [11] and as a substrate for biopolymers' production [12] .…”
Section: Introductionmentioning
confidence: 99%